O financiamento das vendas a prazo no varejo: análise econômica recente das estratégias entre redes varejistas e bancos privados com atuação no Brasil - Moraes, Marcel Castro de (2007)
This research objects to analyze a very visible phenomenon in Brazilian economy in the last years: the strategy alliances between the retail commerce and the financial institutions. Starting from an analysis based on the theory of the financial capital from Rudolph Hilferding and in the conception of credit by the view of Joseph Stiglitz, the possible determinant factors for the consolidation of the phenomenon are discussed. It is important to emphasize that, although the study investigates two factories with different economics activities, retail commerce and banks, the emphasis of the analysis is given to that first sector and not to the last one. The sample of retail dealer chains analyzed is formed by 28 (twenty eight) firms of the sector, where 17 (seventeen) of these companies provided not only information related to the strategic alliances established with banks, but also indicated financial data related to the activity of borrowing offer and/or selling financing to the consumer public. It was verified than, that according to the collected information with the investigated sample, two factors had fundamental relevance to the consolidation of the alliances: the compromise of capital and the risk related to the offer of credit from the retail dealer chains.